Peran Lingkungan Dan Pola Asuh Orang Tua Terhadap Pembentukan Karakter Anak Usia Dini (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
Early childhood is the golden age of the golden age period for the development of all aspects of life, including physical, cognitive, social emotional and character building in children. In the formation of early childhood character, it requires an important role in parenting, where the role of parents is the main pillar in early childhood education, character in early childhood can develop by getting good stimulus and vice versa if bad stimulus is given then This will form a bad character for early childhood, because early childhood has a spontaneous attitude that cannot distinguish between good behavior and bad behavior. As for external influences that can shape early childhood characters, namely the environmental influence, the environment itself is divided into three parts, namely the family environment, school, and community. The research method used in this research is descriptive qualitative research. There are several data collection techniques that the researchers conducted in this study, which include structured observation, semi-structured interviews using a questionnaire schedule or interview guide used in conducting interviews with research sources.